2014
DOI: 10.3126/ojn.v4i1.11307
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Frictional forces between different Archwire-bracket Combinations

Abstract: Introduction: During sliding mechanics, frictional resistance is an important counterforce to orthodontic tooth movement; which must be controlled to allow application of light continuous forces. objective:To investigate static and kinetic frictional resistance between three orthodontic brackets: ceramic, self-ligating, and stainless steel, and three 0.019×0.025" archwires: stainless steel, nickel-titanium, titanium-molybdenum. Materials & Method:The in vitro study compared the effects of stainless steel, nick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…According to the findings, the metallic orthodontic wire presented a greater frictional resistance than the esthetic wires. Previous studies 5,[15][16][17][18] have shown that esthetic brackets have reduced roughness and lower friction when compared to conventional stainless-steel brackets. In the scientific literature, the studies analyzing the frictional resistance of different brackets have reported inconsistent findings due to the different methodologies used, in particular: orthodontic wires and brackets of different manufacturers, different combinations of bracket and wire, distinct test conditions (dry or saliva/other solutions-moistened environment), and different bracket angulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the findings, the metallic orthodontic wire presented a greater frictional resistance than the esthetic wires. Previous studies 5,[15][16][17][18] have shown that esthetic brackets have reduced roughness and lower friction when compared to conventional stainless-steel brackets. In the scientific literature, the studies analyzing the frictional resistance of different brackets have reported inconsistent findings due to the different methodologies used, in particular: orthodontic wires and brackets of different manufacturers, different combinations of bracket and wire, distinct test conditions (dry or saliva/other solutions-moistened environment), and different bracket angulations.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors make it difficult to compare the results between the studies. In general, the smoother surface of the ceramic brackets is believed to contribute to less resistance to friction and mechanical sliding 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Friction can reduce available forces up to 40%, which causes loss of anchor. [5][6][7] Corrosion in the beta titanium wire can also cause titanium ion release that can cause hypersensitivity reactions in some individuals. Studies report that sensitivity to titanium is between 0.6% and 5% in the general population.…”
Section: Introductionmentioning
confidence: 99%